Early diagnosis of relapse in borderline leprosy: two case reports - Brandão, Maria Luiza Figueiredo Braga; Lima, Cíntia Maria Oliveira; Piñeiro-Maceira, Juan; Miranda, Alice; Oliveira, M.Leide W. de (Revista do Instituto de Medicina Tropical de São Paulo, 2011)
Two cases of relapse in borderline leprosy were reported. Despite the late-reversal, reaction-like feature, the suspicion of relapse in both was based on persistent and slow-developing skin lesions and an absence of acute neuritis or reaction during one year of follow-up. The authors have considered this possible occurrence in lepromatous borderline-treated patients after their immune cellular restoration and defend that not all Type 1 reactions would be an inflammatory answer to persistent Mycobacterium leprae, but that they could be. Therefore, a relapse diagnosis could be applied and it is more advisable, as one year of Multi-Drug Therapy (MDT) is less dangerous and more efficient for these cases than one year of corticosteroids.